Affective Taxonomy Domain Development for Improving Elementary Student Behaviour with English Mother Tongue Interaction - Pamuji, Wirawan; Julia Marfuah; Nirmayanti (Indonesian Journal of Contemporary Multidisciplinary Research, 2024)
Contextualized Methods are applied during an advance completing progress in adequate application for English Language applied for the function not for the theory The Research applies Descriptive Qualitative Methods in developing Domain of Affective Taxonomy in measuring how English applied at class with good steps of changing unwell behavior of students at class. Due that English learning process in Asia requires understandable pattern called second acquisition in which most teachers should follow adaptive comprehension in adequate manners of teaching